At-Tafrîq Al-Qadhâ’i And The Religious Courts’ Authority In Deciding A Divorce - A. Zamakhsyari Baharuddin; Rifqi Qowiyul Iman (Universitas Islam Negeri Antasari Banjarmasin, 2020)
AbstractOne of the reasons for the broken marriage is a talaq as a husband's prerogative right. However, in some conditions the talaq is not done by the husband even though the marriage relationship has lost its essence and has gone bad. It is called at-tafrîq al-qadhâ'i which is a way out for the husband's arbitrariness that the Judge is given the authority to terminate the marriage relationship even without the husband’s willingness. This research used a library research method. This research was normative juridical law research and it was analyzed using descriptive-analytic methods. From this research it was found that the Judiciary was authorized to break the rope of marriage through at-tafriq al-qadha’i under certain circumstances to protect the wives’ rights. The authority was not only legally valid in the state law but also had its legitimacy regulated in fiqh.Keywords: tafriq, authority, divorce, judge, the religious courtAbstrakDiantara sebab terputusnya tali pernikahan adalah dikarenakan talak yang merupakan hak prerogatif suami. Namun dalam beberapa kondisi, ternyata talak tidak kunjung dijatuhkan oleh suami meski hubungan pernikahan telah hilang kemaslahatannya bahkan membawa kepada kemudharatan. At-tafrîq al-qadhâ’i yang merupakan jalan keluar dari kesewenangan suami dimana Hakim diberi kewenangan untuk memutuskan hubungan pernikahan tersebut meski tanpa adanya kerelaan dari pihak suami. Penelitian ini menggunakan metode penelitian pustaka (library research). Sedangkan bila dilihat dari sifatnya, penelitian ini termasuk penelitian hukum yuridis normatif yang dianalisis dengan menggunakan metode deskriptif analitik. Dari penelitian ini dapat dinyatakan bahwa Peradilan berwenang untuk memutus tali pernikahan melalui at-tafriq al-qadha’i dalam keadaan tertentu dalam rangka melindungi hak-hak istri. Bahwa kewenangan tersebut selain sah secara hukum negara ia juga memiliki legitimasinya sendiri yang diatur dalam fikih.Kata kunci: tafriq, kewenangan, perceraian, hakim, pengadilan agama